Tailored Exercise Training Counteracts Muscle Disuse and Attenuates Reductions in Physical Function in Individuals With Amyotrophic Lateral Sclerosis - Ferri, Alessandra; Lanfranconi, Francesca; Corna, Giovanni; Bonazzi, Riccardo; Marchese, Samuele; Magnoni, Andrea; Tremolizzo, Lucio (Frontiers in Physiology, 2019)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disease, characterised by the progressive loss of motor neurons, which leads to a reduction in muscle mass, strength, and exercise capacity. Although the concept of “Exercise is Medicine” is accepted for many diseases, the role of exercise in individuals with ALS is still debated. The aim of this study was to propose an exercise training program that was both safe and effective for individuals with ALS, and to evaluate the effects of this combined, moderate-intensity, aerobic and strength training program on aerobic capacities, strength, and physical function. Sixteen individuals with ALS were randomly assigned to either a training (3 times a week for 12 weeks; TRAIN, n=8) or usual care (continued their usual standard of care and served as control; UC, n=8) group. Peak power, peak oxygen uptake, as well as the gas exchange threshold (GET) during a cardiopulmonary exercise test on a cycle ergometer, and the maximal strength of the knee extensor muscles, were evaluated before and after 12 weeks. Participants also performed the “Timed Up and Go” (TUG) and the “6-min walking” (6MWT) tests. The ALS Functional Rating Scale revisited (ALSFRS-R), the ALS Severity Scale (ALS-SS), and the McGill quality of life questionnaire were also measured. The GET increased from 0.94±0.08 to 1.06±0.10 L min-1 in TRAIN (p= 0.009) and decreased from 0.79±0.17 to 0.72±0.17 L min-1 in UC (p= 0.001). There was a significant difference between groups for changes in TUG (9.1±5.5% improvement in TRAIN and 56.8±18.5% worsening in UC, p= 0.002), ALSFRS-R (4.7±2.6% decrease in TRAIN and 23.0±5.6% decrease in UC, p= 0.007), and for the ALS-SS (2.2±2.1% decrease in TRAIN and 12.4±4.4% decrease in UC, p= 0.04). This study showed that a combined moderate-intensity aerobic and strength training program, tailored to the physical capacities of each individual, can counteract muscle deconditioning, improve aerobic fitness, and maintain physical function in individuals with ALS.